EARLY CHILDHOOD ISLAMIC EDUCATION IN DISRUPTION ERA - Aulia Wahyunisa (Sunan Kalijaga International Journal on Islamic Educational Research, 2019)
Islamic Education for Early Childhood should be based on the values of manners, characters or moral animated by the Al-Quran and Sunnah. Achieving manners, characters or the perfect moral are the real purpose of education. Additionally, manners, characters or morality is a basic foundation of one's life in society and the state. The purpose of this paper is to know more clearly what is Early Childhood Islamic Education (PIAUD), and how these concepts in disruption era. The conclusion is the Early Childhood Islamic Education will get more from a family environment, education as a preparation for the child to live in the larger environment, the people. The education should be given to early children is 1) Faith Education and Investment 2) Worship Education and Investment 3) Character Education and development. The Islamic concepts of early childhood education in the era of disruption must start from the family as the first education for children. And the things that must be waged to the families in order to instill the concept of Islamic education itself are: 1) Parents should understand their roles and responsibilities; 2) Family as the first education for children; 3) Commitment to being a good educator for children: 4) Modelling the Prophet as an example; 5) Choose a good school for the children; 6). Being a parent does not have to know everything. And all the concepts of Islamic education will be given to the children by doing the method of habituation, modelling, giving good advice, every attitudes should be punished or rewarded, ordering and prohibiting.